In vitro propagation and mutation induction of torch ginger (Etlingera elatior J.) - Yunus, Muhamad Fahmi (2013)
The aim of this study was to develop a protocol for in vitro propagation and mutation induction of Etlingera elatior by using gamma ray irradiation. The study included establishment an efficient in vitro plant propagation system in E. elatior,investigation of the optimum dose for radio sensitivity test, to determine the effects of various doses of gamma irradiation on multiple bud induction and also to determine the variation in genomic DNA of regenerated shoots by using random amplification of polymorphic DNA (RAPD) technique. In this study, an efficient and systematic protocol for complete plant regeneration from suckers of Etlingera elatior (J.) has been developed. The addition of N6-benzyl amino-purine (BAP) (0, 3, 5, 7 and 10 mg L-1) to the culture medium comprising of Murashige and Skoog (MS) basal salts, 3% sucrose, 0.4% gelrite did not show any significant effects on percentage of shoot induction and mean number of shoots produced. However, BAP at 3 mg L-1 was chosen as the best medium for shoot induction due to economic feasibility and it gave the highest result in all four parameters recorded. Various concentrations of BAP, 6-furfurylaminopurine (kinetin) and N6-(2-isopentenyl) adenine (2-iP) alone at 0, 3, 5, 7 and 10 mg L-1 were tested for shoot multiplication. BAP at all levels were found suitable for the multiplication of shoot. However, the low level of 3 mg L-1 BAP was chosen as the best concentration of BAP due to economic feasibility. The best root proliferation was observed on MS medium without plant growth regulator (PGR). Assessment of various potting media for acclimatization showed medium containing soil: sand: peat moss (1:1:1) produced high survival of plantlets, number of leaves produced per plant and the plant height. Mutation breeding techniques in combination with tissue culture and molecular marker methods provide a powerful tool for improvement of vegetatively propagated plants. The results of irradiation on in vitro buds of E. elatior showed that LD50 to be 10 Gy with the survival of explants being sharply reduced after this dosage. The gamma irradiated shoots were subcultured for three cycles (M1V1 to M1V3) to obtain potential mutant lines. This study showed that RAPD marker was efficient in differentiating the induced mutants from the untreated control of E. elatior. All eight selected gamma irradiated regenerants were differentiated from the untreated control based on the banding patterns obtained using 9 primers which generated 59 reproducible bands, whereby 35 (55.31%) were found to be polymorphic. The Jaccard’s coefficient of similarity values ranging from 0.537 to 0.860 were indicative of the level of genetic variation among the mutants studied. For comparison between the potential lines (PL) and the control, a maximum similarity value (0.814) was observed in PL1 mutant while the minimum value (0.537) was observed in PL7. The presence of polymorphic bands in 8 potential lines suggested that genetic variation occurred in all the treatments as compared to the control. In summary, the combination of techniques of in vitro propagation, multiplication, gamma irradiation, and RAPD analysis for early screening of mutants can facilitate breeding programme of E. elatior.